GPS/GLONASS Combined Precise Point Positioning With the Modeling of Highly Stable Receiver Clock in the Application of Monitoring Active Seismic Deformation. Issue 5 (16th May 2018) - Chen, X.; Lu, C.; Guo, B.; Guo, F.; Ge, M.; Li, X.; Schuh, H.
Abstract: The high‐rate kinematic Precise Point Positioning (PPP) of the Global Navigation Satellite System has become an effective method for monitoring crustal deformation caused by earthquakes. In this contribution, the method of GPS/GLONASS PPP with the receiver clock modeling is applied in active seismic deformation monitoring for the first time. With the modeling method, the short‐term vertical positioning accuracy of 2–4 mm that usually cannot be obtained by standard PPP is achieved. Our PPP results confirm that the positioning accuracy is improved due to the increase of GLONASS observations compared to the GPS‐only solution. Based on the external seismic data and the high‐rate GPS/GLONASS data for the 2011 Japan earthquake and 2010 and 2015 Chile earthquakes, comparative analyses concerning receiver clock modeling are carried out. The results show that a high degree of decorrelation between the height position estimates and receiver clock offsets can be obtained by using the receiver clock modeling. The short‐term accuracy of the GPS‐based vertical displacements is improved to the level of about 4.4 mm, and the short‐term accuracy of better than 4 mm for the GPS/GLONASS‐combined vertical displacements is achievable. Furthermore, the weak vertical signals that are not detected by standard PPP can be captured with the modeling of highly stable receiver clock. Key Points: GPS/GLONASS combined PPP with receiver clock modeling is applied in the field of seismic deformation monitoring for the first time The positioning accuracy of GPS‐only PPP with receiver clock modeling can be improved due to introducing GLONASS The short‐term PPP accuracy of better than 4 mm for vertical seismic displacements is achievable with receiver clock modeling